Analysis of a D-Shaped Photonic Crystal Fiber Sensor with Multiple Conducting Layers - Amanda F. Romeiro; Markos P. Cardoso; Caua C. Miranda; Anderson O. Silva; João C. W. A. Costa; M. Thereza R. Giraldi; Jose L. Santos; Jose M. Baptista; Ariel Guerreiro (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract In our study, we conducted a thorough analysis of the spectral characteristics of a D-shaped surface plasmon resonance (SPR) photonic crystal fiber (PCF) refractive index sensor, incorporating a full width at half maximum (FWHM) analysis. We explored four distinct plasmonic materials-silver (Ag), gold (Au), Ga-doped zinc oxide (GZO), and an Ag-nanowire metamaterial-to understand their impact on sensor performance. Our investigation encompassed a comprehensive theoretical modeling and analysis, aiming to unravel the intricate relationship between material composition, sensor geometry, and spectral response. By scrutinizing the sensing properties offered by each material, we laid the groundwork for designing multiplasmonic resonance sensors. Our findings provide valuable insights into how different materials can be harnessed to tailor SPR sensing platforms for diverse applications and environmental conditions, fostering the development of advanced and adaptable detection systems. This research not only advances our understanding of the fundamental principles governing SPR sensor performance but also underscores the potential for leveraging varied plasmonic materials to engineer bespoke sensing solutions optimized for specific requirements and performance metrics.